Education For Community Transformation: The Influence of Socio-Cultural Practices Toward Schooling of Young Maasai Women of Monduli District -Tanzania - Madodi, Mussa (Papanda Publisher, 2024)
The Tanzanian Government has made several efforts to guarantee the accessible and equitable education to all children irrespective of their race, creed or sex. However, there are some predominant socio-cultural practices which are impediments to young women’s education. Using a case of Monduli district -Tanzania, this study explored the influence of socio-cultural practices toward schooling of Maasai Young Women. A cross- sectional research design was adopted to obtain a sample of 120 respondents. Data were collected using Questionnaires, Key Informants’ Interview (KII) and Focus Group Discussions (FGDs) methods and analysed by using IBM-SPSS. 20.0 and content analysis. Overall, the study found that, Nomadic Lifestyle, Female Genital Mutilation (FGM) and Early Marriages are tremendously affecting schooling of young Maasai women. While the two earlier mentioned practices were found to waste a lot of girls’ learning hours; the latter has been causing a substantial number of school girls to drop out. Subsequently the girls became vulnerable to illiteracy of which jeopardizes their chances to participate in community development projects as well as in decision-making process. The illiterate people are not always invited to participate because they do not understand the nitty gritty of their participation. In order to eliminate these harmful practices, it is recommended the government and other stakeholders to create or strengthening community awareness campaigns and capacity-building programs.